Sámi language in Norwegian healthcare: “He speaks good enough Norwegian, I don’t see why he needs an interpreter” - Engnes, Janne Isaksen; Sivertsen, Nina; Bongo, Berit Andersdatter; Mehus, Grete (Scandinavian Journal of Caring Sciences, 2021)
Introduction: The Indigenous people of Norway are legally entitled to use their Sámi language in encounters with healthcare services, yet these encounters are generally conducted in Norwegian language. The right to Sámi language and culture in health is particularly relegated when Sámi healthcare personnel is not present. This neglect of Sámi language and culture in the Norwegian healthcare system impacts on the quality of care Sámi patients receive. Aim: This paper describes and interprets healthcare interactions between nurses and Sámi-speaking patients in Norway. Method: Qualitative semi-structured focus group interviews were conducted with Sámi (n = 13) and Norwegian nurses (n = 10). Participants were included if they had experience working with Sámi-speaking patients and two years clinical practice in the Sámi area of northern Norway. Interpretive and descriptive analyses were conducted. Findings: Obtaining only basic patient information and lack of mapping of native language in admission documents or patient notes makes it challenging to recognise Sámi patients. In encounters with Sámi patients, Norwegian nurses must navigate linguistic challenges with an additional layer of interplay between culture and care. Misunderstandings in this area can undermine patient safety and be directly contrary to health legislation and patient rights. As remedy, Sámi nurses often improve the nurse–patient dialogue by translating and explaining cultural nuances, thus improving understanding of healthcare interactions, and bridging the gap to the Norwegian staff. Conclusion: To integrate Sámi language and culture into nursing care new guidelines to implement knowledge of Sámi patients’ culture and language rights in healthcare education is needed. In addition, the authorities have to facilitate implementation of laws and regulations, research and guidelines in practical health care. At last, the number of Sámi-speaking nurses has to increase.